PERSEPSI MASYARAKAT TERHADAP PERPANJANGAN 9 TAHUN MASA JABATAN KEPALA DESA ( Studi Pada Kecamatan Rambutan Kabupaten Banyuasin) - Susanto, Heri; Darmawan, Erik (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research discusses public perceptions regarding the extension of the village head’s term of office by 9 years in the Rambutan Subdistrict of Banyuasin Regency. In light of demonstrations by village heads demanding an extension of their terms, the researcher aims to understand how the community perceives this extension. The study aims to analyze public perceptions of extending the village head’s term from 6 to 9 years in the Rambutan Subdistrict of Banyuasin Regency. The research method used is descriptive qualitative. Data collection techniques involve interviews with village heads, community leaders, and residents. However, it’s important to note that while the majority of the community agrees with extending the village head’s term to nine years, this consensus doesn’t always imply positive impacts. Further analysis reveals that the agreement is primarily influenced by feudal societal norms, a lack of understanding about democracy, and limited political education.